2005
DOI: 10.1523/jneurosci.4505-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Spider Peripheral Mechanosensory Neurons Are Directly Innervated and Modulated by Octopaminergic Efferents

Abstract: Octopamine is a chemical relative of noradrenaline providing analogous neurohumoral control of diverse invertebrate physiological processes. There is also evidence for direct octopaminergic innervation of some insect peripheral tissues. Here, we show that spider peripheral mechanoreceptors are innervated by octopamine-containing efferents. The mechanosensory neurons have octopamine receptors colocalized with synapsin labeling in the efferent fibers. In addition, octopamine enhances the electrical response of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 50 publications
3
48
1
Order By: Relevance
“…We showed previously that information capacity in spider mechanoreceptor neurons rises as the firing rate is increased by current injection (French et al, 2001), octopamine (Widmer et al, 2005), or GABA A agonists (Pfeiffer et al, 2009). Here, we asked whether this increased information capacity is caused by decreased jitter or by other mechanisms.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…We showed previously that information capacity in spider mechanoreceptor neurons rises as the firing rate is increased by current injection (French et al, 2001), octopamine (Widmer et al, 2005), or GABA A agonists (Pfeiffer et al, 2009). Here, we asked whether this increased information capacity is caused by decreased jitter or by other mechanisms.…”
Section: Introductionmentioning
confidence: 96%
“…Neuromodulation can increase or decrease excitability, as seen by changes in membrane potential and action potential firing rates (Matheson, 1997;Page and Blackshaw, 1999;Rudomin and Schmidt, 1999;Torkkeli and Panek, 2002;Birmingham et al, 2003;Widmer et al, 2005). It can also affect dynamic properties of neuronal responses or spontaneous firing patterns (Ramirez et al, 1993;Matheson, 1997;Birmingham et al, 2003;Pfeiffer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The efferent fibers contain GABA, glutamate, and acetylcholine, which all inhibit the responses of sensory neurons to step mechanical or electrical stimuli (FabianFine et al 2002;Panek and Torkkeli 2005;Panek et al 2002;Widmer et al 2006). Octopamine is also present in some of the efferent fibers and octopamine application has an excitatory effect on neuronal activity (Widmer et al 2005). Intracellular recordings from neurons of VS-3 lyriform slit sensilla in the spider patella ) and a simulated model based on these recordings showed that GABAergic inhibition can be achieved by shunting or inactivation of Na channels and that these two factors can combine to cause stronger inhibition.…”
Section: Introductionmentioning
confidence: 99%
“…A larger value of k indicates a greater sensitivity to high frequencies and more rapid adaptation. An increase in information capacity R was previously observed in spider mechanosensory neurons when the firing rate increased (French et al 2001;Widmer et al 2005). Graphical comparisons of AP rate and amplitude as well as membrane potential (E m ) before and after muscimol application are also shown in Fig.…”
Section: Muscimol Application Results In a Triphasic Response In Firimentioning
confidence: 58%
“…The 50-to 300-m-long sensory dendrites are attached to the slits via a specialized cuticular structure . Peripherally located parts of these neurons are surrounded by thin efferent fibers (FabianFine et al 1999) that have been shown to contain GABA, glutamate, and octopamine (Fabian-Fine et al 1999Widmer et al 2005).…”
Section: Introductionmentioning
confidence: 99%